A Descriptive Analytical Study Of The Effect Of Traumatic Brain Injury Patient Transport Protocols On Rates Of Neurological Deterioration During Field Transport In The Saudi Red Crescent (The Review of Diabetic Studies, 2025)
This analytical descriptive research paper sought to examine the impact of patient transportation procedures in case of traumatic brain injury (TBI) on the rate of neurological deterioration during transportation in the field of the Saudi Red Crescent. The sample population was 200 paramedics, who were chosen through different emergency field units. The research instrument was a designed questionnaire that was subdivided into three aspects namely, (1) implementation of transportation protocols, (2) monitoring during transportation, and (3) competence, training, and the quality of performance. The analysis of data was conducted with the help of descriptive statistics (mean, standard regression) and One-Way ANOVA to demonstrate the significant differences between dimensions. The findings showed that the general commitment to TBI transport protocols is high, as the implementation and monitoring mean (2.62) and (2.61) are high. Nonetheless, the dimension of training and competence had a moderate mean (2.53), which indicates that the constant development of a professional should happen. RCA test revealed that there was a statistically significant difference between the three dimensions (F = 4.28, Sig = 0.015) showing that there is variation in the degree of compliance and operational consistency. Altogether, the findings point to the efficient use of TBI transport protocols and the presence of commitment to the patient monitoring in the field transport in the Saudi Red Crescent. Nonetheless, the findings indicate the significance of routinely performing enhancing training, periodically reviewing performances, and enhancing documentation practices to guarantee patient safety and neurological decline in emergency transport.